Privacy under threats: an analysis on the online risks and legal measures in protecting privacy of children online - Abd. Jalil, Juriah (2014)
Privacy, either personal or informational, is increasingly under threats in this digital age. Adult and children alike are victims of prying eyes in the virtual world and without us realising it, a private message or photograph that is posted even within a password secured transaction, can become a public matter within seconds with detrimental effects on the owner. As a result our looks and personality as well as our private and personal information may be used, abused, manipulated and exposed to online dangers such as theft of identity, cyber stalkers, cyber bullying and victims of ridicule. Children, as regular and active Internet users, are constantly exposed to severe online risks. They can become the target of paedophiles, sexual groomers, and perpetrator of child pornography who often trespass into the privacy of the children’s email, Facebook address or short message service (SMS), even chatroom by faking identity to pursue their criminal intent. Children are also found to be receiving inappropriate online commercial advertising in their emails. In some jurisdiction, cyber bullying, online ridicule and involvement with paedophiles had led to the death of several youth victims. In all the instances, Social network service (SNS), youtube, instant message (IM) and SMS have been identified as the common modus operandi of the manipulator or the criminals. As a result jurisdiction like the US, UK and South Korea have either extended the application of paper based law that protect privacy to online world, or enacted specific internet law or imposed legal liability on the Internet Service Providers (ISPs) to ensure privacy of children are protected. This paper therefore aims to highlight the threats of online risks on the privacy of children and discusses the legal measures and approach adopted in some jurisdictions to protect privacy of children in line with the United Nation Convention on the Rights of A Child. This paper submits that the protection of privacy of children online is crucial and all means especially legal measure is an important tool to ensure the protection is guaranteed.